Fairy Baby Spa / Amirah Saidin ... [et al.] - Saidin, Amirah; Zabli, Fatimah; Sulaiman, Norfalahani; Pelong, Nur Siti Baizurah; Mansur, Maziera Safiza (2014)
The name of our company is Fairy Baby Spa Sdn. Bhd. Our business is based on partnership which includes 5 persons who have certain qualification in business management and wide knowledge about Spa.Our spa is not like a commonly spa but it exclusively only serve baby around age 1 until 5 year. The main services in our company are baby swim, baby bath, baby massage, haircut, ear clean, and nail cut. The selection of "Fairy Baby Spa" as our company's name is simply because we acts like a fairy that would fulfill the needed and desire of our customer. The focus of our Fairy Baby Spa is to strengthening and stimulating babies to improve their physical growth and mental development so they can maintain their metabolism in normal rate, beside that our company is a reasonable-price spa that provides a maximum flexibility and strong customer attention along with our trademark "we care we treat". By using this strategy, fairy baby spa would fulfill baby needs and market demand will be increase. Our target customers are people around Sabah, this is because in Sabah there no specific place for baby to do special treatment like spa, so our business will be the first ever company in Borneo that would serve only babies which will be the new market for the entire entrepreneur out there. Our proposed location for business operation will be placed in Suria Sabah and be expecting to commence on June 2014. We choose this location because the location is in city and in shopping mall, thus it wills more convenience for the customer to come here andthey do not have to worry about where they want to park their car as there are many parking lots provided. Beside that this placed is more safe that other because there are many security guards guarding.